Implementation of Teachers' Strategies in Strengthening Religious Character in SMPN 2 Aralle Mamasa District - Tasbi, Amal; Jufri, Muhammad; M, Amiruddin; Firman, Firman; Musyarif, Musyarif (Abjadia : International Journal of Education, 2025)
This study aims to describe the teacher's strategy in strengthening the religious character of students at SMPN 2 Aralle, as well as identifying the form of religious character that develops and the factors supporting its success. This research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results showed that the strengthening of religious character is carried out through a holistic approach that includes habituation of religious activities, exemplary teachers, integration of religious values in learning, and extracurricular activities such as flash Pesantren and tadarrus Al-Qur'an. Learners show religious behaviours such as honesty, discipline, responsibility, and empathy. The success of the programme is supported by the active role of the principal, teachers, parents, the availability of infrastructure and facilities, and a supportive school culture. The findings show that a collaborative and contextual approach can effectively shape learners' religious character in a sustainable manner. This research contributes to the development of a participatory school-based religious character education model.